EP982 Management of indeterminate pelvic masses and borderline ovarian tumours: a survey of current practice of gynaecological oncology centres in the united kingdom. (1st November 2019) - Jones, R; Howells, R; Rzyska, E; Lim, K; Sharma, A
Abstract : Introduction/Background: Borderline ovarian tumours (BOT) represent approximately 15% of ovarian tumours. Currently there is no clear guidance on management or follow up, leading to variation in practice. We aimed to assess current practice in gynaecological oncology centres around the United Kingdom. Methodology: We surveyed the membership of the British Gynaecological Cancer Society (BGCS) via an online survey platform from 01/11/2017–30/06/2018. A single reminder was sent during the collection period. Information was gathered about use of frozen section for indeterminate mass at laparotomy, surgery offered for those who were post-menopausal or with family completed versus those wanting fertility sparing, offer of completion surgery for those who had initial fertility sparing surgery, whether an agreed protocol for follow up of BOT was in place, length of follow up and whether adjuvant treatment is offered. Data analysis was with Microsoft Excel. Results: Responses were received from 19 of the 33 (58%) UK gynaecological oncology centres. 13 (72%) centres reported frozen section use. 18 (95%) centres reported offering total abdominal hysterectomy and bilateral salpingo-oophorectomy for women who were post-menopausal or reported their family was complete. All 19 centres reported offering fertility sparing surgery in those where family not completed. 16 (89%) centres reported offering completion surgery for those who had initial fertility sparing surgery. 16 (89%) centres reported having an agreed protocol for follow up of BOT. Only 5 (28%) centres reported offering adjuvant treatment depending on presence of invasive implants or advanced disease with 12 (67%) not offering any additional treatment. Conclusion: Based on responses there is variation in the management of indeterminate pelvic masses and borderline ovarian tumours between centres. These findings suggest that there is a need to develop a UK wide management strategy to provide uniformity of care. Disclosure: Nothing to disclose.